A modified tacho-less order tracking method for the surveillance and diagnosis of machine under sharp speed variation. (October 2018) - Wu, Jie; Zi, Yanyang; Chen, Jinglong; Zhou, Zitong
Highlights: A modified TLOT technique based on nonlinear compensating demodulation transform was proposed. NCDT can accurately estimate the instantaneous frequency of machine. The modified TLOT is verified by simulations, experiments and industrial cases. The proposed method can accurately extract the fault feature of mechanical equipment in the process of sharp speed variation. Abstract: Tacho-less order tracking (TLOT) is an effective technique to address the surveillance and diagnosis of mechanical fault on speed variation conditions without tachometers. Nevertheless, fault diagnosis with sharp speed fluctuations is still a challenging task, since the accurate instantaneous frequency (IF) cannot be obtained from the acquired condition signals. In this work, a modified TLOT method based on nonlinear compensating demodulation transform (NCDT) is proposed for fault diagnostics in extreme condition monitoring of machinery. During NCDT, the demodulation functions based on opposite cubic polynomial are investigated and performed to improve IF estimation. Then, a regression filter (RF) is employed to extract the interested harmonic component according to the estimated IF and instantaneous bandwidth for signal resampling. Finally, order spectrum analysis is used to analyze the resampled signal for mechanical fault diagnosis. Simulations, experiments and industrial cases are given to verify the effectiveness and efficiency of the proposed method. The results are as effective as those obtained by tacho-based method under sharp speed fluctuation.